Variability for growth, flowering and fruit set in seedling progenies of nutmeg (Myristica fragrans Routt.) - C Haldavnekar, P M Haldankar, G D Joshi, B P Patil, P (Journal of Spices and Aromatic Crops, 2004)
The variability in growth, flowering and fruit set of 39 seedling progenies of nutmeg (Myristica fragrans) was studied at Ratnagiri (Maharashtra). Growth was cyclic with two peaks, one in January-February and the second in May. Shoot elongation was rapid during lS0-270 days after shoot emergence during first peak. Considerable variation among the genotypes with respect to growth parameters was noticed. Duration of anthesis was short in female flowers and long in male flowers. Significant variations were noticed among genotypes for duration of anthesis and fruit set. Environmental coefficient of variation was very low for fruit set and duration of anthesis. Higher magnitudes of phenotypic coefficient of variation and genotypic coefficient of variation indicated good amount of variation among the genotypes for these characters. High estimates of heritability and genetic advance for fruit set suggested that it is under the control of additive gene action.